2022
DOI: 10.2147/ppa.s374808
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin Adherence Among Patients with Atrial Fibrillation in Rural Area of Dongyang, China: A Questionnaire-Based Study

Abstract: Introduction Adherence to warfarin is associated with improved outcome in patients with atrial fibrillation (AF), but the adherence status of patients in rural areas of China is not known. Methods A questionnaire-based study evaluating warfarin adherence of rural residents with AF was carried out in Dongyang, China. Potentially eligible patients were screened and contacted by telephone, and their demographic characteristics were collected. Illness perception was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…A lack of adherence to warfarin medication may make it difficult to keep the INR value within the desired range, which could lead to issues like excessive or subtherapeutic bleeding risks or excessive anticoagulation, which raises the risk of stroke and thromboembolic events. Chen et al [13] found that 47.3% of those who received warfarin treatment had good compliance. Tülek et al [14] reported that 79.8% of the patients had high compliance Similarly, in our study, adherence to drug treatment was good in both groups, which we think is due to the telephone application reminding patients to use the drug.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of adherence to warfarin medication may make it difficult to keep the INR value within the desired range, which could lead to issues like excessive or subtherapeutic bleeding risks or excessive anticoagulation, which raises the risk of stroke and thromboembolic events. Chen et al [13] found that 47.3% of those who received warfarin treatment had good compliance. Tülek et al [14] reported that 79.8% of the patients had high compliance Similarly, in our study, adherence to drug treatment was good in both groups, which we think is due to the telephone application reminding patients to use the drug.…”
Section: Discussionmentioning
confidence: 99%